Dutch scientists and the UNESCO Statement on Race - Harkema, Bram; Sysling, Fenneke (Studium, 2019)
Central to this paper is a survey held among Dutch scientists in 1951 after the publication of the first UNESCO Statement on Race. The Statement, issued by a committee of experts at UNESCO, was a condemnation of scientific racism and declared that race was a social myth. The statement led to strong international criticism from physical anthropologists and geneticists, who disagreed with the dismissal of the concept of race and because they were poorly represented on the committee of experts. This paper traces the reception of the first Declaration on Race among scientists in the Netherlands to demonstrate how the Statement’s impact differed in different contexts. The survey about the Statement organized by Dutch anthropologists shows how Dutch racial scientists used the Statement to distance themselves from Nazi racial science by employing a rhetoric of humility, insistence on the difference between scientific findings and moral choices, suggestions for alternative conceptualizations of race, and a strategic internationalism to connect with the international community of experts. The success of this strategy can be concluded from the fact that one of the organizers of the Dutch survey, physical anthropologist Rudolf Bergman, was invited, very last minute, to participate in the expert meeting of biological scientists that formulated a second UNESCO Statement on Race, issued a year after the first.